2023
DOI: 10.3390/cells12131684
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Advanced Glycation End Products: Their Role in the Insulin Resistance of Aging

Abstract: Insulin resistance (IR) is commonly observed during aging and is at the root of many of the chronic nontransmissible diseases experienced as people grow older. Many factors may play a role in causing IR, but diet is undoubtedly an important one. Whether it is total caloric intake or specific components of the diet, the factors responsible remain to be confirmed. Of the many dietary influences that may play a role in aging-related decreased insulin sensitivity, advanced glycation end products (AGEs) appear part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…AGEs have been shown to induce insulin resistance, inflammation, and oxidative stress, all well-known key features of PCOS. Recent studies have examined the role of AGEs in insulin resistance and found that AGEs can impair insulin signaling pathways, resulting in decreased insulin sensitivity [35,36] . This finding suggests that AGEs play a causal role in developing insulin resistance, a characteristic feature of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…AGEs have been shown to induce insulin resistance, inflammation, and oxidative stress, all well-known key features of PCOS. Recent studies have examined the role of AGEs in insulin resistance and found that AGEs can impair insulin signaling pathways, resulting in decreased insulin sensitivity [35,36] . This finding suggests that AGEs play a causal role in developing insulin resistance, a characteristic feature of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating AGE levels are positively correlated with insulin resistance in humans 26 . Dietary AGEs promote insulin resistance 27 . Moreover, CML accumulates in the skeletal muscles of diabetic rats, 28 and glycated albumin causes a pro‐inflammatory response in muscle cells 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated blood sugar levels have the potential to give rise to advanced glycation end products, which have the ability to amass in the brain and result in oxidative stress and inflammation. These factors are known to play a role in CI [ 53 ].…”
Section: Introductionmentioning
confidence: 99%